2023
DOI: 10.37349/etat.2023.00176
|View full text |Cite
|
Sign up to set email alerts
|

Melatonin, BAG-1 and cortisol circadian interactions in tumor pathogenesis and patterned immune responses

George Anderson

Abstract: A dysregulated circadian rhythm is significantly associated with cancer risk, as is aging. Both aging and circadian dysregulation show suppressed pineal melatonin, which is indicated in many studies to be linked to cancer risk and progression. Another independently investigated aspect of the circadian rhythm is the cortisol awakening response (CAR), which is linked to stress-associated hypothalamus-pituitary-adrenal (HPA) axis activation. CAR and HPA axis activity are primarily mediated via activation of the g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 219 publications
(396 reference statements)
0
4
0
Order By: Relevance
“…Chen et al . and Anderson demonstrated that MLT could suppress the translocation of glucocorticoid receptors and increase the expression of SIRT3, thereby modulating autophagy and mitophagy and inhibiting OP progression 105,106 . These findings provided a more comprehensive understanding of how MLT may serve as a therapeutic agent in counteracting OP.…”
Section: Discussionmentioning
confidence: 89%
See 1 more Smart Citation
“…Chen et al . and Anderson demonstrated that MLT could suppress the translocation of glucocorticoid receptors and increase the expression of SIRT3, thereby modulating autophagy and mitophagy and inhibiting OP progression 105,106 . These findings provided a more comprehensive understanding of how MLT may serve as a therapeutic agent in counteracting OP.…”
Section: Discussionmentioning
confidence: 89%
“…Chen et al and Anderson demonstrated that MLT could suppress the translocation of glucocorticoid receptors and increase the expression of SIRT3, thereby modulating autophagy and mitophagy and inhibiting OP progression. 105,106 These findings provided a more comprehensive understanding of how MLT may serve as a therapeutic agent in counteracting OP. Muxel et al observed NF-kB-mediated enhancement of macrophage phagocytosis through MLT synthesis, which contributes to the functional specialization of macrophages that is essential for the innate immune defense.…”
Section: Discussionmentioning
confidence: 95%
“…Thus, the immunoenhancing action of MLT is linked to its circadian properties, including the receptor-mediated modulation of cytokine production, cell migration and antigen presentation to immunocompetent cells [ 44 , 45 ]. Last but not least, MLT may suppress the nuclear translocation of glucocorticoid receptors [ 46 ] and, hence, modulate their effect on immunity [ 47 ].…”
Section: Melatonin and The Immune Systemmentioning
confidence: 99%
“…This effect involves the stimulation of cytokines such as IL-1β, IL-2, IL-6, IL-8, TNF-α, IFNγ and IL-17A and/or the upregulation of cyclooxygenase-2 (COX-2) and inducible NO synthase. Other effects are exerted on hematopoiesis by stimulating GM-CSF and the differentiation of Th cells and NK cells [ 46 ]. Yet, an excessive inflammatory response may have a paradoxical effect on immunity, leading to the activation of the coagulation system, organ failure and immunodeficiency by inducing T-cell apoptosis [ 49 ].…”
Section: Melatonin and The Immune Systemmentioning
confidence: 99%
“…Generally, CAR, along with the corelease of adrenal aldosterone, is proposed to increase respiration and blood pressure in 'preparation for the coming day' [40]. However, recent work indicates that CAR may be an important regulator of pathophysiology across diverse medical conditions, including neurodegenerative conditions and cancer, as well as aging [41,42]. The GR is typically held in a cytoplasmic complex with heat shock protein (hsp)90 and p23.…”
Section: Stress Hpa Axis and Morning Cortisol Awakening Responsementioning
confidence: 99%